Maternal Immune Activation Affects Hippocampal Excitatory and Inhibitory Synaptic Transmission in Offspring From an Early Developmental Period to Adulthood - Nakagawa, Keiju; Yoshino, Hiroki; Ogawa, Yoichi; Yamamuro, Kazuhiko; Kimoto, Sohei; Noriyama, Yoshinobu; Makinodan, Manabu; Yamashita, Masayuki; Saito, Yasuhiko; Kishimoto, Toshifumi (Frontiers in Cellular Neuroscience, 2020)
One of the risk factors for schizophrenia is maternal infection. We have previously shown that Polyriboinosinic-polyribocytidylic acid (poly I:C) induced maternal immune activation in mice caused histological changes in the hippocampal CA1 area of offspring during the developmental period and impaired sensorimotor gating in offspring during adulthood, resulting in behavioral changes. However, it remains unclear how maternal immune activation functionally impacts the hippocampal neuronal activity of offspring. We studied the effect of prenatal poly I:C treatment on synaptic transmission of hippocampal CA1 pyramidal cells in postnatal and adult offspring. Treatment with poly I:C diminished excitatory and enhanced inhibitory (GABAergic) synaptic transmission on pyramidal cells in adult offspring. During the early developmental period, we still observed that treatment with poly I:C decreased excitatory synaptic transmission and potentially increased GABAergic synaptic transmission, which was uncovered under a condition of high extracellular potassium-activated neurons. In conclusion, we demonstrate that maternal immune activation decreased excitatory and increased inhibitory synaptic transmission on hippocampal pyramidal cells from an early developmental period to adulthood, which could result in net inhibition in conjunction with poor functional organization and integration of hippocampal circuits.